Analisis Daya Tarik Wisata Pendukung Kawasan Gunung Api Purba Nglanggeran, Yogyakarta - Nuviah Herawati; Susilo Budi Winarno (Journal of Tourism and Economic, 2020)
This study aims to find out supporting activities that arise with the use of the ancient Nglanggeran volcano landscape in the Nglanggeran Village. Nglanggeran tourism village in Yogyakarta has a variety of supporting tourism potential attractions that arises due to the construction of an artificial pond / reservoir. This reservoir is the main capital for the local community to create supporting attractions which are a major complement to the ancient volcanic landscape of Nglanggeran. The emergence of these supporting attractions subsequently becomes a source of profit for the community and especially tourism activities in the region.